2017
DOI: 10.33012/2017.15036
|View full text |Cite
|
Sign up to set email alerts
|

Improved Linear Direct Solution for Asynchronous Radio Network Localization (RNL)

Abstract: In the field of localization the linear least square solution is frequently used. This solution is compared to nonlinear solvers more effected by noise, but able to provide a position estimation without the knowledge of any starting condition. The linear least square solution is able to minimize Gaussian noise by solving an overdetermined equation with the Moore-Penrose pseudoinverse. Unfortunately this solution fails if it comes to non Gaussian noise. This publication presents a direct solution which is able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…34 Alternatively, the nonlinear system can be transformed into a linear system. 9,10 With the assumptions made in Section 2.1, it is possible to obtain a linear system. With regard to future extensions to determining the base station positions as well as the location of the object T, this article focuses on finding a solution with a non-convex optimization algorithm.…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…34 Alternatively, the nonlinear system can be transformed into a linear system. 9,10 With the assumptions made in Section 2.1, it is possible to obtain a linear system. With regard to future extensions to determining the base station positions as well as the location of the object T, this article focuses on finding a solution with a non-convex optimization algorithm.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…With known reference station positions, it is possible to transform the quadratic to a linear system. [9][10][11] This linear system can be used to provide an initial estimate. On the other hand, the linear system is more affected by noise, compared with the quadratic system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio Ra linearly increased with M. In contrast to the UWB, it was necessary to calculate the offset analytically for the LPM, as well. The linear estimation that we used can be found in [18]. This linear solution was expanded by the ability to operate with the additional dimensionsλ i , λ j andλ.…”
Section: Partially-analytical Methodsmentioning
confidence: 99%
“…The important disadvantage of the LPM equation was that all data were strongly affected by the offset O j , which changed from one measurement to the next. In [18], we showed that subtracting one measurement from another eliminated the offset and had some significant advantages for data filtering. In contrast to the UWB, it was also necessary to calculate the offset analytically for the LPM.…”
Section: Real Measurementsmentioning
confidence: 99%